STUDENT VOLUNTEER ACTIVITIES TO SUPPORT CHILDREN WITH ASD - I. M. Yakovleva; O. V. Karanevskaya; Yu. A. Afanasieva (Высшее образование в России)
This article reveals the importance ofvolunteer activities performed by students (future special pedagogues) and analyses experience of organization student volunteer support for children with Autistic Spectrum Disorder in educational organizations implementing inclusive practice. The authors focus on the realization of the educational project "Inclusive molecule: technologies of supporting children with ASD in conditions of educational organization" started in September 2015. The project was aimed at formation of students' professional competences in the sphere of special pedagogy and inclusive practice. The volunteer activities included three stages: 1) preparatory, 2) pedagogical support of children with ASD during the inclusive practice, 3) reflexive analysis of students' practical pedagogical experience. The authors give concrete proposals aimed at raising the efficiency of students' participation in volunteering projects.